Source Of Latest Anti-TB Treatment Amongst Re-Treatment TB Cases Registered Under RNTCP In Gujarat - Dave, P; Rade, K; Pujara, KR; Solanki, Rajesh; Modi, Bhavesh; Patel, PG; Nimavat, P (National Journal of Community Medicine, 2011)
Introduction: Despite sustained performance in case detection and success rate under Revised National TB Control Programme for >5 years, higher proportion of re-treatment cases has been observed amongst smear positive cases in Gujarat. Objective: To find out the source of re-treatment TB cases registered for treatment under DOTS under RNTCP to indirectly estimate role of private sector in treating TB patients. Methods: Cross-sectional study. Review of records and reports & data from TB treatment cards was compiled and analyzed (Secondary data source) Results: Proportion of re-treatment cases having latest type of anti-TB treatment under DOTS were 63% as compared to 37% of non-DOTS regimens. Amongst those who had received DOTS as latest treatment re-treatment registration as relapse was highest with 58% while it was Treatment After default with 44% as highest proportion amongst those with non-DOTS as latest anti-TB regimens. There was high correlation between the type of registration of re-treatment in the year 2010 and the outcomes reposted for year 2009 cohorts under DOTS for treatment after default and failures. There is a definite negative correlation between ratio of DOTS: non-DOTS as latest regimen history amongst the re-treatment TB cases registered and the New Smear Positive TB case registrations. Conclusion: Though RNTCP has achieved programme objectives at state level since more than 5 years in Gujarat, there exists a huge case load of Tuberculosis in private sector. Higher proportion of relapse registrations from DOTS sources can be attributed to high number of patients successfully treated on previous occasions. Default still is the major concern in non-DOTS regimens.